Health impacts of changes in travel patterns in Greater Accra Metropolitan Area, Ghana. (October 2021) - Garcia, Leandro; Johnson, Rob; Johnson, Alex; Abbas, Ali; Goel, Rahul; Tatah, Lambed; Damsere-Derry, James; Kyere-Gyeabour, Elvis; Tainio, Marko; de Sá, Thiago H.; Woodcock, James
Highlights: Increase in car trips can lead to 400 extra deaths and 20, 500 YLL per year. Rise in motorcycles can lead to 370 extra deaths and over 18, 500 YLL per year. Changes to bus trips can avert over 600 deaths and 31, 500 YLL per year. Road traffic fatalities were the largest contributor to changes in deaths and YLL. Abstract: Background: Health impact assessments of alternative travel patterns are urgently needed to inform transport and urban planning in African cities, but none exists so far. Objective: To quantify the health impacts of changes in travel patterns in the Greater Accra Metropolitan Area, Ghana. Methods: We estimated changes to population exposures to physical activity, air pollution, and road traffic fatality risk and consequent health burden (deaths and years of life lost prematurely – YLL) in response to changes in transportation patterns. Five scenarios were defined in collaboration with international and local partners and stakeholders to reflect potential local policy actions. Results: Swapping bus and walking trips for car trips can lead to more than 400 extra deaths and 20, 500 YLL per year than travel patterns observed in 2009. If part of the rise in motorisation is from motorcycles, we estimated an additional nearly 370 deaths and over 18, 500 YLL per year. Mitigating the rise in motorisation by swapping long trips by car or taxi to bus trips is the most beneficial for health, averting more than 600 premature deaths and over 31, 500 YLL per year. Without significant improvements in road safety, reduction of short motorised trips in favour of cycling and walking had no significant net health benefits as non-communicable diseases deaths and YLL benefits were offset by increases in road traffic deaths. In all scenarios, road traffic fatalities were the largest contributor to changes in deaths and YLL. Conclusions: Rising motorisation, particularly from motorcycles, can cause significant increase in health burden in the Greater Accra Metropolitan Area. Mitigating rising motorisation by improving public transport would benefit population health. Tackling road injury risk to ensure safe walking and cycling is a top priority. In the short term, this will save lives from injury. Longer term it will help halt the likely fall in physical activity.